PSIKOLOGIS KEPRIBADIAN DAN SOSIAL ANAK DALAM KELUARGA DENGAN STATUS PERKAWINAN SIRI - Rudy Catur Rohman; Muhammad Maddarik (MAQASHID, 2022)
Siri marriage, a form of marriage that is not officially registered with the state but is recognized as legitimate under certain religious laws, is a common phenomenon in Indonesia. This practice has significant psychological and social implications for children born from such unions. The study aims to analyze the impact of siri marriage on the psychological and social development of children, focusing on how the uncertainty of the parents' marital status affects the children's well-being. The findings suggest that children from siri marriages often struggle with issues such as low self-esteem, identity confusion, and emotional instability. They are more susceptible to psychological disorders, including anxiety and depression, due to the social and emotional uncertainty they experience. Moreover, the stigma attached to their parents' marital status often leads to social isolation, hindering their ability to form healthy interpersonal relationships and adapt to their social environments. The study emphasizes the importance of parental and social support to mitigate these negative effects and foster emotional stability in children. It also calls for legal and social interventions to better protect the rights and welfare of children born from siri marriages.